2018
DOI: 10.3389/fimmu.2018.01370
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide and Programmed Death-1 Blockade Synergistically Enhances the Effects of Dendritic Cell Vaccination in a Model of Murine Myeloma

Abstract: The therapeutic efficacy of dendritic cell (DC)-based immunotherapy may be potentiated in combination with other anticancer therapies that enhance DC function by modulating immune responses and the tumor microenvironment. In this study, we investigated the efficacy of DC vaccination in combination with lenalidomide and programmed death (PD)-1 blockade in a model of murine myeloma. MOPC-315 cell lines were injected subcutaneously to establish myeloma-bearing mice and the following five test groups were establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…The fundamental goal of immunotherapy in the treatment of MM is to boost tumor-specific immunity and eliminate malignant cells. Based on in vitro and preclinical studies, DC-based tumor vaccines have the potential to induce antimyeloma immunity mediated by CTLs ( 11 , 35 ). However, eliciting a clinically meaningful antitumor effect is challenging and the results remain inconclusive, with validation required in larger prospective randomized controlled studies ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental goal of immunotherapy in the treatment of MM is to boost tumor-specific immunity and eliminate malignant cells. Based on in vitro and preclinical studies, DC-based tumor vaccines have the potential to induce antimyeloma immunity mediated by CTLs ( 11 , 35 ). However, eliciting a clinically meaningful antitumor effect is challenging and the results remain inconclusive, with validation required in larger prospective randomized controlled studies ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models of myeloma are known to play a critical tool for studying the mechanisms of disease resistance, pathogenesis, and the development of new therapeutics against malignancies ( 35 , 40 – 42 ). This study has some limitation to interpret data due to subcutaneous injection of MOPC-315 cells for making plasmacytoma rather than BM involvement model for myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…200-205 The latter include (1) immune checkpoint blockers such as the anti-PD-1 mAbs pembrolizumab and nivolumab, 206-208 the anti-PD-L1 mAbs durvalumab and atezolizumab, 209-211 and the anti-CTLA4 mAb ipilimumab; 137,186,212-215 (2) immunostimulatory antibodies such as utomilumab, which stimulates TNF receptor superfamily member 9 (TNFRSF9; best known as 4-1BB or CD137) signaling, 28,216-218 or the CD27 agonist varlilumab; 28,216,219,220 and immunomodulatory agents such as lenalidomide. 221-224 In line with preclinical and clinical data demonstrating that multi-epitope vaccines are generally more powerful than their single-epitope counterparts, 117,225 the most common vaccination strategy employed by these studies consists in targeting simultaneously multiple TAAs (20 studies). Alongside, 15 studies are investigating the safety and efficacy of PPV, often consisting of MHC-matched peptides chosen from the immune repertoire of the patient before treatment.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…An early study showed lenalidomide suppressed the secretion CCL2 from NLCs and inhibited the survival support of NLCs for CLL cells in vitro [84]. A recent in vivo study showed that lenalidomide in combination with dendritic cell vaccination and anti-PD-1 blocking antibody decreased M2-TAMs with an associated reduction in TGF-β and IL-10 in the spleen of myeloma-bearing mice [85]. In several clinical trials for B-cell lymphoma, lenalidomide showed promising clinical efficacy either as a single agent or in combination with other immunotherapeutic agents [86][87][88][89].…”
Section: New Macrophage-targeting Therapies In Hematologic Malignanciesmentioning
confidence: 99%